Sosialisasi Wawasan Pasar Pengiriman Kargo Internasional 2021 - Budi Nur Rochmadi; Christianto Eka Wiguna; Peppy Fachrial (Jurnal Abdimas Transportasi & Logistik, 2022)
The Covid-19 pandemic that occurred in 2020 had a major impact on the socio-economic life of the community by implementing social distancing programs in several countries. The impact of the world economy occurs with a contraction of -5% in 2020 (UNCTAD, 2021). Nationally, the economic contraction occurred at -2.07% (BPS, 2021a). In general, the national export and import industry (EXIM) has been hard-hit by increasing international transportation prices, scarcity of transportation equipment and imbalance in transport capacity. The impact also continues in early 2021, when the economy starts to pick up, fueling demand for international transportation but does not keep pace with the recovery of transport capacity. The purpose of this webinar is to provide information to exim players about international transportation and effective solutions from hands-on practitioners working in the field of freight forwarding. The material presented here is drawn from the market prospects, transportation reports, global research and KWE internal reports. With these materials, the information provided in the webinar becomes more actual. The response to the webinar was very positive. In general, the exim industry players are helped by the information provided. Several participants also eager to know when the capacity imbalance will be resolved.